THE ACADEMICIAN N.I. VAVILOV AND INTRODUCTION OF RICE IN RUSSIA - A. V. Chamyshev (Зерновое хозяйство России, 2018)
The article considers the role of N.I. Vavilov in creating the theory of introduction of plants. N.I. Vavilov was the first who showed the possibility and practicability of expanding rice from the southern parts of the country to the northern ones – Povolzhie, North Caucasus and the Far East. According to his theory of introduction there are such forms of rice which are suitable for growing in other regions with other conditions. At the first stage he recommended using the early maturing Japanese rice varieties. According to him the success of the introduction of rice is determined by the variety, the environmental conditions and especially by the cultivation technology, which significantly affect on the efficiency of use of ecologic factors. Thereby the prospects have been shown to grow rice in the new rice growing regions during the flooding and during the periodic watering. The ideas of N.I. Vavilov about the introduction of plants are very urgent in this country and t the modern stage of plant-growing development.